2019
DOI: 10.3892/ol.2019.10345
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑410‑3p upregulation suppresses proliferation, invasion and migration, and promotes apoptosis in rhabdomyosarcoma cells

Abstract: Rhabdomyosarcoma (RMS) is one of the most common types of soft tissue sarcoma in children; however, the pathogenesis of RMS is unclear. MicroRNAs (miRs) are involved in the development and progression of RMS. The role of miR-410-3p in RMS cell invasion, migration, proliferation and apoptosis, and its possible mechanism were investigated in the current study. Reverse transcription-quantitative polymerase chain reaction and western blot analysis were performed to detect the expression of miR-410-3p in RMS tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…In this study, we found that miR-365 expression was higher in adult sheep than in sheep embryos, indicating that the gene may be involved in inhibiting the myoblast proliferation. We also observed that oar-miR-410-3p expression was very high during the embryonic stage, which was in agreement with another study that found that miR-410-3p overexpression suppressed invasion, migration, and proliferation, downregulated EMTassociated molecule expression, and promoted apoptosis and apoptotic factor expression in rhabdomyosarcoma cells (Zhang et al, 2019). There have been many functional studies on the four lncRNAs, linc-MD1 (Legnini et al, 2014;Yoon, Abdelmohsen & Gorospe, 2013), Yam-1 (Li et al, 2018;Simionescu-Bankston & Kumar, 2016, sirt1AS (Ming et al, 2016Wang et al, 2016), and H19 (Dey, Pfeifer & Dutta, 2014;Gao et al, 2014), involved in muscle development.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that miR-365 expression was higher in adult sheep than in sheep embryos, indicating that the gene may be involved in inhibiting the myoblast proliferation. We also observed that oar-miR-410-3p expression was very high during the embryonic stage, which was in agreement with another study that found that miR-410-3p overexpression suppressed invasion, migration, and proliferation, downregulated EMTassociated molecule expression, and promoted apoptosis and apoptotic factor expression in rhabdomyosarcoma cells (Zhang et al, 2019). There have been many functional studies on the four lncRNAs, linc-MD1 (Legnini et al, 2014;Yoon, Abdelmohsen & Gorospe, 2013), Yam-1 (Li et al, 2018;Simionescu-Bankston & Kumar, 2016, sirt1AS (Ming et al, 2016Wang et al, 2016), and H19 (Dey, Pfeifer & Dutta, 2014;Gao et al, 2014), involved in muscle development.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that miR-365 expression was higher in adult sheep than in sheep embryos, indicating that the gene may be involved in inhibiting the myoblast proliferation. We also observed that oar-miR-410-3p expression was very high during the embryonic stage, which was in agreement with another study that found that miR-410-3p overexpression suppressed invasion, migration, and proliferation, downregulated EMT-associated molecule expression, and promoted apoptosis and apoptotic factor expression in rhabdomyosarcoma cells (Zhang et al, 2019). There have been many functional studies on the four lncRNAs, linc-MD1 (Legnini et al, 2014;Yoon et al, 2013), Yam-1 (Li et al, 2018;Simionescu-Bankston & Kumar, 2016), sirt1AS (Ming et al, 2016;Wang et al, 2016), and H19 (Dey et al, 2014;Gao et al, 2014), involved in muscle development.…”
Section: Discussionsupporting
confidence: 92%
“…These authors also displayed that transcription factor Snail is a direct target of miR-410-3p and in this way miR-410-3-p inhibits an EMT process. MiR-410-3p has been demonstrated to inhibit the invasion and migration of rhabdomyosarcoma cells through inhibiting EMT [ 151 ]. Wang and other authors suggested that miR-410 function in CRC may be connected to negative regulation of DKK-1 through Wnt/β-catenin pathway [ 152 ].…”
Section: Discussionmentioning
confidence: 99%